Neonatal sepsis and transient immunodeficiency: Potential for novel immunoglobulin therapies? - Beudeker, Coco R.; Vijlbrief, Daniel C.; van Montfrans, Joris M.; Rooijakkers, Suzan H.M.; Flier, Michiel van der (Frontiers in Immunology, 2022)
Neonates, especially preterm neonates, have the highest risk of sepsis of all age groups. Transient immaturity of the neonatal immune system is an important risk factor. Neonates suffer from hypogammaglobulinemia as nor IgA nor IgM is transferred over the placenta and IgG is only transferred over the placenta late in gestation. In addition, neutrophil numbers and complement function are also decreased. This mini-review focuses on strategies to improve neonatal host-defense. Both clinical and preclinical studies have attempted to boost neonatal immunity to lower the incidence of sepsis and improve outcome. Recent advances in the development of (monoclonal) antibodies show promising results in preclinical studies but have yet to be tested in clinical trials. Strategies to increase complement activity seem efficient in vitro but potential disadvantages such as hyperinflammation have held back further clinical development. Increase of neutrophil numbers has been tested extensively in clinical trials but failed to show improvement in mortality. Future research should focus on clinical applicability of promising new prevention strategies for neonatal sepsis.